Effects of Financial Literacy and Fintech P2P on Warung Business Development: Fintech Adoption Study at Aksesmu - Dendy Wibowo; Hans Harischandra Tanuraharjo; Christian Haposan Pangaribuan (PT Publikasiku Academic Solution, 2025)
This study examines the influence of performance expectancy and facilitating conditions on the behavioral intention to adopt financial technology among MSME grocery stall owners, while also assessing the moderating role of financial literacy in these relationships. Using a survey method, data were collected from 231 MSME grocery stall owners in Greater Jakarta, West Java, Central Java, and East Java who have experience with P2P fintech services. The data were analyzed using the Structural Equation Modeling (SEM) approach with SmartPLS software. The results show that performance expectancy and facilitating conditions each have a positive and significant effect on behavioral intention to use P2P fintech, whereas financial literacy does not significantly moderate these relationships. These findings provide an empirical basis for designing more effective and inclusive P2P fintech service strategies for the MSME sector and highlight the importance of enhancing financial literacy and digital technology adoption in the microbusiness context.